Economic Potential Study on the Agricultural Sector as a Leading Sector in Central Java Province, Indonesia - Hutajulu, Dinar Melani; Septiani, Yustirania; Sugiharti, Rr Retno; Indrawati, Lucita Rita; Sarfiah, Sudati Nur (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2025)
The agricultural sector is the third-largest contributor to Central Java’s GRDP and continues to grow annually. Despite this, labor absorption in agriculture remains low, and the declining farmer’s exchange rate indicates worsening farmer welfare. This study aims to analyze the economic base, growth potential, and sectoral mapping of agriculture in Central Java. The research employs several analytical tools including Location Quotient (LQ), Growth Ratio Model (GRM), Overlay Analysis, and the BCG Matrix. Results show that sub-sectors such as food crops, horticulture, livestock, and agricultural and hunting services are the economic base of the region, maintaining their relevance both before 2019 and after 2022 the COVID-19 pandemic. Among them, horticulture demonstrates strong growth potential, while food crops, livestock, and agricultural services also show opportunities for development. The BCG Matrix further highlights horticultural crops and agricultural services as the primary drivers of growth. These findings suggest that targeted government support and policy prioritization toward these key sub-sectors are essential for sustaining agricultural advancement and improving farmer welfare in the region.